THEORETICAL FOUNDATIONS OF THE ORGANIZATION OPERATIONS IN BANKS (World Economics and Finance Bulletin, 2023)
Due to the fact that it is not possible to determine the amount of reduction from the book value of the old replaced or partially damaged buildings in buildings or buildings that have been capitally repaired by commercial banks. Today, in most cases due to such issues, the balance sheet value of buildings and structures that have been capitally repaired by commercial banks is increased due to the costs of repairs. This, in turn, has a negative impact on the financial results of commercial banks with property tax, building and construction depreciation costs. Therefore, it is important to develop theoretically based practical suggestions on this issue
Keywords: asset; active operations; bank